2013
DOI: 10.1055/s-0033-1350898
|View full text |Cite
|
Sign up to set email alerts
|

Catechol Conjugates Are In Vivo Metabolites of Salicis cortex

Abstract: After oral administration of 100 mg/kg b. w. (235.8 µmol/kg) salicortin to Wistar rats, peak serum concentrations of 1.43 mg/L (13.0 µM) catechol were detected after 0.5 h in addition to salicylic acid by HPLC-DAD after serum processing with β-glucuronidase and sulphatase. Both metabolites could also be detected in the serum of healthy volunteers following oral administration of a willow bark extract (Salicis cortex, Salix spec., Salicaceae) corresponding to 240 mg of salicin after processing with both enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Salicinoids have been suggested to be activated by degradation to the toxic metabolite saligenin (reviewed in Pentzold et al, 2014) or catechol, which may oxidize to form reactive quinones (Ruuhola et al, 2001). These reactions were proposed based on the results of in vitro experiments (Clausen et al, 1990;Julkunen-Tiitto and Meier, 1992;Ruuhola et al, 2003) and studies with bacteria (Sonowal et al, 2013;Zhu et al, 1998) or vertebrates (Knuth et al, 2013;McLean et al, 2001), but the pathways of salicinoid metabolism in poplar-feeding arthropods are still not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Salicinoids have been suggested to be activated by degradation to the toxic metabolite saligenin (reviewed in Pentzold et al, 2014) or catechol, which may oxidize to form reactive quinones (Ruuhola et al, 2001). These reactions were proposed based on the results of in vitro experiments (Clausen et al, 1990;Julkunen-Tiitto and Meier, 1992;Ruuhola et al, 2003) and studies with bacteria (Sonowal et al, 2013;Zhu et al, 1998) or vertebrates (Knuth et al, 2013;McLean et al, 2001), but the pathways of salicinoid metabolism in poplar-feeding arthropods are still not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In early in vitro studies using intestinal sections of normal and antibiotic-treated rats, Fötsch and Pfeifer found that intestinal bacteria are able to degrade salicin to saligenin (Fötsch and Pfeifer, 1989 ). However, in in vivo pharmacokinetics studies in humans, the main salicin metabolite salicylic acid was already detectable in serum 1 h after oral administration of salicin or WBE, suggesting that salicin is obviously already absorbed in the stomach or upper intestinal tract and hydrolyzed before or during absorption (Schmid et al, 2001 ; Knuth et al, 2013 ). Similar results were obtained when the salicin derivative salicortin was orally administered to rats (Knuth et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In plasma, the main metabolite of salicyl alcohol derivatives is salicylic acid, together with minor amounts of salicyluric acid and gentisic acid (Schmid et al, 2001 ). In addition, catechol sulfate was observed as a salicortin metabolite in serum (Knuth et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1] does not claim a specific willow species for the drug, but insists on a minimum amount of 1.5% salicylic alcohol derivatives, there is a great variety in willows which can be used for the drug Salicis cortex. Although it is known that these salicylic alcohol derivatives are metabolized to the anti-inflammatory compound salicylic acid in vivo [4,5], there is doubt that only this class of secondary plant ingredients is responsible for the effects described above [2,3] as the resulting in vivo concentration is much too low to explain the overall efficacy of willow bark [5]. As not only anti-inflammatory but also cooperative effects are described for proanthocyanidins (PA) [6,7], which are one of the main groups of Salix ingredients beside the salicylic alcohol derivatives and flavonoids [3], it is necessary to investigate each willow species to broaden the knowledge about the complete phenolic spectrum of these important compounds.…”
Section: Introductionmentioning
confidence: 99%